EFFECT OF COMBINED THYROXINE AND CORTISOL TREATMENT ON HATCHING OF EGGS, POST-EMBRYONIC GROWTH AND SURVIVAL OF LARVAE OF HETEROPNEUSTES FOSSILIS - Nayak, P. K.; Mishra, T. K.; Mishra, J.; Pandey, A K. (Journal of Indian Fisheries Association, 2015)
In order to record the effects of thyroxine and cortisol (individual/ combined) on hatching, post-embryonic growth and survival of larvae of Heteropneustes fossilis, newly fertilized eggs were given bath immersion treatments of L-thyroxine (T4; 0.05 mgfl), cortisol (0.50 mgll) and T4+ cortisol (0.05 mgll +0.50 mgfl) for 15 days. Hatching of eggs, growth and survival of the larvae improved significantly (P < 0.001) in the hormone treated groups as compared to those of control. The frequency of deformities was reduced in the combined hormone treatment group. The present observations suggest that the advanced digestive function probably induced by T4+cortisol treatment might have resulted in improvement in food utilization during the critical phases of first feeding and promoted vital developmental processes resulting in uniform growth, decreased mortality, better survival and transformation of larvae to juveniles. This combined hormone therapy appears to have practical utility in fish hatchery practice for better success in larval rearing. Keywords: Thyroxine (T4), cortisol, larvae, survival, growth,Heteropneustes fossilis